A framework for developing user-based adaptive gamified systems - Wael Elgammal; Nada Sherief; Walid Abdelmoez (Advances in Computing and Engineering, 2023)
Gamification, which is the use of game elements in a non-game context, has become a trend in many industries. It is used as means for motivating and engaging users and influencing their behaviors. Thus, during the last few years many researchers have attempted to find a way to design and implement gamified systems that are adaptively personalized based on user types. This paper proposes a framework that aims to aid software engineers in systematically designing adaptively personalized gamification applications of any context type by adapting the appearance of gamification elements based on each user type. The framework introduces a method that provides a systematic means to modify the system at runtime (i.e. while the system is in use) based on the user’s preferences and behavior by changing the existing elements based on the usage of each user.  We validate the proposed framework using a case study conducted with employees of a large-scale software development company. By applying all their practical comments, the methods of the proposed framework were enhanced. Moreover, to formalize the proposed framework we develop an ontology that implements the mappings between game elements and user types by defining rules that govern their usage. In this paper, an ontology validation is presented including the use of Reasoner, Instances, SPARQL queries, and requirements model implementation. Also, a sample prototype is presented on one of the most used application and show how we apply this framework on it. Received: 13 June 2023 Accepted: 16 September 2023 Published: 20 October 2023